2005
DOI: 10.1161/01.str.0000177867.39769.cb
|View full text |Cite|
|
Sign up to set email alerts
|

Associations of the Angiotensin II Type 1 Receptor A 1166 C and the Endothelial NO Synthase G 894 T Gene Polymorphisms With Silent Subcortical White Matter Lesions in Essential Hypertension

Abstract: Background and Purpose-Silent white matter lesions (WMLs) may represent early target organ damage of the brain in patients with hypertension. Because these lesions may have a genetic background, we assessed the associations between polymorphisms of the renin-angiotensin system and the endothelial NO synthase (NOS3) genes and silent WMLs. Methods-Ninety-three hypertensive individuals were studied. MRI of the brain was performed to obtain estimates of the total volume of subcortical and the extent of periventric… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
34
1
3

Year Published

2008
2008
2024
2024

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(38 citation statements)
references
References 41 publications
0
34
1
3
Order By: Relevance
“…47 Data for meta-analyses were unavailable in 2 of relevant studies (922 subjects, ie, 34% of the total number of subjects), but neither found a significant association (Figure 4). 40,46 Fixed-effect meta-analyses for all these genetic polymorphisms produced similar results. Polymorphisms in many of the other genes that had been studied in much fewer numbers showed preliminary evidence for an association with WMH (eg, CYP11B2, protein kinase on chromosome 19, and intercellular adhesion molecule 1), but far larger samples will have to be studied to confirm or refute these preliminary findings.…”
Section: Resultsmentioning
confidence: 59%
See 3 more Smart Citations
“…47 Data for meta-analyses were unavailable in 2 of relevant studies (922 subjects, ie, 34% of the total number of subjects), but neither found a significant association (Figure 4). 40,46 Fixed-effect meta-analyses for all these genetic polymorphisms produced similar results. Polymorphisms in many of the other genes that had been studied in much fewer numbers showed preliminary evidence for an association with WMH (eg, CYP11B2, protein kinase on chromosome 19, and intercellular adhesion molecule 1), but far larger samples will have to be studied to confirm or refute these preliminary findings.…”
Section: Resultsmentioning
confidence: 59%
“…16,24,29,[37][38][39][40][41][42] Six compared numbers of subjects with upper and lower WMH grades between genotype groups (Figure 2A). 16,29,37,38,42 Random-effects meta-analysis comparing deletion-deletion (DD) with deletion-insertion/ insertion-insertion (DI/II) suggested a significant association between ACE and WMH (pooled OR, 1.95; 95% CI, 1.09 -3.48), but there was substantial heterogeneity between study results (I 2 ϭ71%).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The polymorphism in the gene for this enzyme is a proposed risk factor for vascular dementia. Polymorphisms in this gene have been associated with increased volume of subcortical white matter lesions (Henskens, Kroon, van Boxtel, Hofman, & de Leeuw, 2005). White matter hyperintensities have been linked to age related changes in memory functioning (Nordahl et al, 2006).…”
Section: Since Vascular and Systemic Disease Can Affect Cognition A mentioning
confidence: 99%